Pelembagaan Hukum Jinayat di Aceh Sebagai Bagian Sistem Hukum Pidana Indonesia - M Ikhwan; Muhammad Heikal Daudy (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2019)
This research seeks to explain the implementation of Islamic law in Aceh, especially the institutionalization Islamic criminal law through the implementation of Jinayat Law as part of the criminal justice system in Indonesia. Positive law in Indonesia is the legal norms derived from Islamic jurisprudence as a result of normative ‘marriage’ between sharia law and local wisdom Indonesia, even though the constitution 1945 did not mention Indonesia as an Islamic state, but Islamic law in Indonesia is living amidst society. Formerly it was only limited to the field of Ahwal Al-Syakhsiyah and Muamalat, however, nowadays partake into the Islamic criminal law (Jinayah). Aceh province is given authority to implement the Islamic jurisprudence (qanun), have since recorded constitution no. 44 of 1999, constitution no. 18 of 2001, and constitution no. 11 of 2006, all of which is a product of positive law governing Indonesia about privileges and specificity of Aceh. This research method using library research and juridical normative legal research with secondary data and use approaches regulations (statute approach). This research concludes that Islamic criminal law (jinayat) that are implemented in Aceh as part of the criminal justice system, which complements the general rules that apply nationally and the law of criminal procedure has not been full of the legal community in Indonesia especially Muslims in Aceh. DOI: https://doi.org/10.5281/zenodo.3467458